Developing collaborative creativity through microblogging: A material-dialogic approach. (September 2020) - Cook, V.; Major, L.; Warwick, P.; Vrikki, M.
Highlights: Novel use of diffractive analysis in the context of technology-mediated dialogue. The phenomena of creativity is materially-discursively performed. A microblogging tool as active collaborator in creative endeavours. Widening the material-dialogic space of collaboration. Abstract: A dialogic theory of collaborative creativity focuses on the emergence of new perspectives from the interplay of 'voices'. With much research on the interaction between digital technology, dialogue and collaborative creativity focusing on human voices, this paper explores how a microblogging tool may contribute to co-creative processes as a 'voice' in a dialogue. We diffractively read excerpts from one lesson, involving learners aged 11–12 years studying English in the UK, through material-dialogic theory and Barad's theory of agential realism. Through our entanglement with both theory and data, we explore the tensions and relationships between: i). ideas of creativity in the context of digital technology-supported classroom dialogue; and ii). frameworks of understanding informed by agential realism. Bringing these two sets of ideas together addresses a gap in our current understanding of the multi-layered nature of students' creative engagement with digital technologies in classrooms. These findings are thus significant when considering a material-dialogic approach in the context of developing collaborative creativity through technology. Additionally, the paper makes a methodological contribution, illustrating the use of a diffractive approach in the context of technology-mediated dialogue and creativity.